Manifestação de dorsalgia entre servidores públicos: a atividade física como ferramenta de auxílio à gestão pública - Silva, Marianne Alves da (2021)
Introduction: The facilities arising from technological advances, contribute to a sedentary lifestyle of the global population, which has consequences for the health and quality of life of individuals. Many chronic diseases are avoided if they forced them to adopt a more active lifestyle, making use of the numerous benefits to recover through the practice of regular physical activity. The problem is that the lack of physical activity has an express impact on the economically active population, as it affects health and quality of life, leading, for example, to leaves and low productivity in the associations they work for. Among the diseases that most drive away economically active people in the world is back pain. Thus, the main objective of this work is to verify the relationship between the regular practice of physical activity and the manifestation of back pain among employees of the Federal University of Espírito Santo (Ufes) in the unit of Alegre, and proportion the implementation of a policy to encourage physical activity practices among them. In theoretical terms, there was a bulletin addressing the public management model that seeks to reduce costs, efficiency and effectiveness in the provision of services and also about the role of public servants in this context. Then, it was relevant to understand concepts such as worker health, back pain, absenteeism, physical activity and worker health, as well as how this is used in the context of public management and at Ufes. As for the methods and procedures, it was to use a quantitative-descriptive approach. Data collection was performed using the Nordic Musculoskeletal Questionnaire (QNSO) and the International Physical Activity Questionnaire (IPAQ), distributed via e-mail. The sample was found by 54 civil servants, including professors and administrative technicians. As a result, it was found that 70.3% of servers are sedentary or insufficiently active, in addition to a prevalence of back pain of 75.9% among servers. There was a statistically significant association between level of physical activity and manifestation of back pain. From the result, the Draft: Server in motion - Ufes / Alegre was prepared as a technical product, containing a proposal for the development of the Server in Movement application and the creation of the Academia para Servers.